Exploring the Impact of WhatsApp, Facebook Usage and Big Five Personality Traits on Scholastic Performance among Secondary School Students - Wajid Mahnaz; Dr Sidra Kiran, (Dialogue Social Science Review (DSSR), 2024)
The Impact of Big Five Personality Traits on usage of WhatsApp, Facebook has gained considerable attention now a days and the reason behind it is growing prevalence of digital platforms in everyday life. Objectives of the study were; 1) To explore the influence of Big Five personality traits on students' engagement with WhatsApp and Facebook for academic purposes. 2) To explore the influence of Big Five personality traits on students' engagement with WhatsApp and Facebook for academic purposes. 3) To analyze the mediating role of Scholastic Performance in the effect of WhatsApp and Facebook usage Personality Traits of secondary school students. All 8617 Students of grade 10th of District Attock, (4,868 Boys & 3,749 Girls) at secondary and higher secondary school level in 248 public schools were the population of the study. 816 students were the sample for this study from the population. Proportional Sampling technique was used for sampling. Big Five Personality Tool consists of 39, Usage of Social Network Sites tool consists of twenty nine different items for five basic and commonly used Social Network Sites. Reliability of the tools was found by using Cronbach’s Alpha. For content validity, both research tools were validated from the experts of field of education while for construct validity, EFA was performed. The findings from the PROCESS procedure (Model 4) offer insights into the relationships between Big Five Personality Traits (BFPTs), Scholastic Performance (SP), and Social Network Sites (SNSs). The analysis shows that BFPTs significantly predict Scholastic Performance (SP), with a positive coefficient of 1.528 (p < 0.01). The model's R-squared value of 0.528 indicates that 52.81% of the variance in Scholastic Performance can be explained by BFPTs. This relationship suggests that students' personality traits are strongly related to their academic performance. Hence, it is recommended that, Interventions should focus on improving both Scholastic Performance and personality traits to help students manage their social media usage effectively.